On the heat transport mechanism and entropy generation in a nozzle of liquid rocket engine using ferrofluid: A computational framework. Issue 4 (12th February 2019) - Acharya, Nilankush; Das, Kalidas; Kundu, Prabir Kumar
Graphical abstract: Abstract: An investigation has been carried out to demonstrate the performance of heat transfer and entropy generation in a regenerative cooling channel of a rocket engine. The Nanofluid flow in composition with ferrous nanoparticles has been utilized. Foremost equations are reduced to its non-dimensional shape using similarity renovation and sketched out using variational iterative method (VIM). Impression of the pertinent factors on hydrothermal performance has been brought forwarded via tables and graphs. Favourable comparison originates the basis of our present work. Result communicates that non-dimensional entropy generation amplifies in response to the parameter R and Bejan number intensifies for the parameter N . Significance or application of the present literature is to provide kerosene based ferrofluid as a coolant of rocket engine and how pertinent factors affect the entropy inside the system. Parametric study of this investigation will aid aerospace engineers to design the regenerative equipment in an effective way.